Sustainability Dalam Rantai Pasok Global: Tinjauan Literatur Dari Perspektif Bisnis Internasional dan Manajemen Rantai Pasok - Ruslaini Ruslaini; Eri Kusnanto (Journal Of Business, Finance, and Economics (JBFE), 2020)
In the context of supply chain management and international business, sustainability in global supply chains is crucial. This literature review synthesizes various studies to explore strategies, outcomes, and challenges related to sustainability initiatives in different organizational settings. The findings highlight the importance of stakeholder engagement, technological innovation, and regulatory compliance in promoting sustainable practices. Additionally, adopting green technologies and collaborating with suppliers are essential for enhancing sustainability and operational efficiency. Integrating Sustainable Development Goals (SDGs) and digital advancements is key to achieving competitive advantage and resilience in global markets.